Data on endogenous bovine ovarian follicular cells peptides and small proteins obtained through Top-down High Resolution Mass Spectrometry - Valérie Labas; Ana-Paula Teixeira-Gomes; Laura Bouguereau; Audrey Gargaros; Lucie Spina; Aurélie Marestaing; Svetlana Uzbekova (Data in Brief, 2017)
The endogenous peptides and small proteins extracted from bovine ovarian follicular cells (oocytes, cumulus and granulosa cells) were identified by Top-down High Resolution Mass Spectrometry (TD-HR-MS/MS) in order to annotate peptido- and proteoforms detected using qualitative and quantitative profiling method based on ICM-MS (Intact Cell Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry). The description and analysis of these Top-down MS data in the context of oocyte quality biomarkers research are available in the original research article of Labas et al. (2017) http://dx.doi.org/10.1016/j.jprot.2017.03.027 [1]. Raw data derived from this peptidomic/proteomic analysis have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository (dataset identifier PXD004892). Here, we described the inventory of all identified peptido- and proteoforms including their biochemical and structural features, and functional annotation of correspondent proteins. This peptide/protein inventory revealed that TD-HR-MS/MS was appropriate method for both global and targeted proteomic analysis of ovarian tissues, and it can be further employed as a reference for other studies on follicular cells including single oocytes. Keywords: Top-down proteomics, Bovine, Ovary, Follicular cells